Application of Chemistry E-Magazine Media to Students' Interest in Learning in Public Senior High School - Gita Aulia Cahyani; wigati, indah; Ravensky Yurianty Pratiwi (Chemistry Education Department of Education and Teaching Faculty, 2024)
This study aims to test the effect of e-magazine chemistry media on students' interest in learning buffer solution material. This research uses a quasi-experimental design. The data collection technique used was an interest questionnaire in the form of 20 statements that were tested for the validity of the items, with the results of all statements being valid and a reliability of 0.811, so the questionnaire has a very high level of reliability. The data analysis was done using a t-test at a sig value. (2-tailed) 0.05 parametric statistical test analysis through SPSS software version 25. The experimental class was given treatment using e-magazine chemistry media, and the control class used textbooks. The experimental class's average pre-test and post test scores were 56.18 and increased to 82, while the control class's scores were 55.26 and increased to 65.26. Based on the results of the study, it was shown that the use of e-magazine chemistry was influenced in learning buffer solution material in terms of the data analysis of 0.000. This study implies that e-magazine chemistry can improve students' interest.